2006
DOI: 10.1007/s11064-006-9128-5
|View full text |Cite
|
Sign up to set email alerts
|

Glycogen Synthase Kinase-3 (GSK3): Inflammation, Diseases, and Therapeutics

Abstract: Deciphering what governs inflammation and its effects on tissues is vital for understanding many pathologies. The recent discovery that glycogen synthase kinase-3 (GSK3) promotes inflammation reveals a new component of its well-documented actions in several prevalent diseases which involve inflammation, including mood disorders, Alzheimer's disease, diabetes, and cancer. Involvement in such disparate conditions stems from the widespread influences of GSK3 on many cellular functions, with this review focusing o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
613
0
8

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 680 publications
(652 citation statements)
references
References 191 publications
(214 reference statements)
13
613
0
8
Order By: Relevance
“…Moreover, Akt activation augments as revealed by the presence of the active form of Akt (phospho-Akt Thr308; pAkt308) ( Figure 1a). 1 Increased Akt activation was accompanied by phosphorylation of its downstream targets β-catenin ser552 (pβ-cat552) 20 and GSK3β Ser9 (pGSK3β) 21 ( Figure 1a). Augmented Akt1 levels were also detected in the mucosa of inflamed mice, but no changes in total β-catenin and GSK3β were observed (Figure 1a).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, Akt activation augments as revealed by the presence of the active form of Akt (phospho-Akt Thr308; pAkt308) ( Figure 1a). 1 Increased Akt activation was accompanied by phosphorylation of its downstream targets β-catenin ser552 (pβ-cat552) 20 and GSK3β Ser9 (pGSK3β) 21 ( Figure 1a). Augmented Akt1 levels were also detected in the mucosa of inflamed mice, but no changes in total β-catenin and GSK3β were observed (Figure 1a).…”
Section: Resultsmentioning
confidence: 99%
“…First, we demonstrated that GSK3b plays a crucial role in apoptosis of osteoblasts caused by GC. In osteoblasts, GSK3b is not only the main actor in osteoblastogenesis [5], but also a multi-tasking regulator in many biological events, including structure, gene expression, mobility, and apoptosis [29,30]. Activation of GSK3b is regulated by serine and tyrosine phosphorylation, by protein complex formation, and by its intracellular localization [22].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the activity of GSK3 has been reported in type II diabetes mellitus and obese animal models (Eldar-Finkelman et al, 1999;Nikoulina et al, 2000). GSK3 is also involved in inflammation that accompanies various kinds of diseases (reviewed in Jope et al, 2007). GSK3 inhibition attenuates activation of the pro-inflammatory transcription factor NF-κB and activates the immunomodulatory transcription factor -catenin (Gong et al, 2008).…”
Section: Pathological Functionmentioning
confidence: 99%